Controlling Friction With External Electric or Magnetic Fields: 25 Examples - Krim, Jacqueline (Frontiers in Mechanical Engineering, 2019)
Studies of the fundamental origins of friction have undergone rapid progress in recent years, providing valuable information on the relative contributions of electronic, magnetic, electrostatic and phononic dissipative mechanisms. They are now evolving into methods that allow active control of nano and/or meso scale friction through tuning of magnetic and electric fields external to the contact. These methods constitute an area of rapidly growing interest, as they address one of tribology’s present day grand challenges: achieving in situ control of friction levels without removing and replacing lubricant materials situated within inaccessible confines of a contact. In this minireview, 25 examples of electromagnetic tuning of friction are overviewed, with examples spanning atomic to macro scale systems to demonstrate the variety and versatility of approaches that have been reported in the literature. Applications include, but are not limited to triboelectric generators, geological drilling, automotive braking and efficiency, spacecraft systems, biological systems and magnetic spintronics. Experimental methods for measuring the impact of electric or magnetic fields on friction include AFM, SFA, QCM, pin-on-disk, hard disk head- substrate, MEMS and NEMS based tribometers, and optical spectroscopies. Computational and theoretical approaches include analytic, equilibrium and nonequilbrium Monte Carlo simulations.